Interval Hysterectomy for Placenta Percreta - a Case Report - Mohammad Sazzadul Huque; Mini Ravi (University Library System, University of Pittsburgh, 2019)
Introduction: Placenta percreta is an abnormality of placentation where it invades the serosa and can go beyond it. Complications include massive hemorrhage, bladder dysfunction, and severe infections during delivery.  The aim of this study is to report a complex case of placenta percreta managed by interval hysterectomy. Case presentation: Pre-operative: 34 years old patient with previous three cesarean sections was followed in antenatal clinic. She came with repeated bouts of vaginal bleeding at 30-31 weeks. At 32 weeks and 4 days classical cesarean section was done with placenta left in situ. Prophylactic bilateral internal iliac artery balloon was inserted. Post cesarean section, uterine artery embolization was performed. Post-operative: Clinical features of pulmonary embolism (PE) developed about 4 hours later. Post-Operative Day 13: Total abdominal hysterectomy was done. After few days of discharge, the patient presented to the emergency department with shortness of breath. She was consequently diagnosed with chronic pulmonary embolism and treated with warfarin. Conclusion: This is a case of placenta percreta managed by interval hysterectomy. However, the most widely accepted method of management is cesarean hysterectomy. In this case, interval hysterectomy was done due to the possibility of bladder invasion by placenta, to decrease the amount of blood loss and to reduce the number of days stayed in hospital. Appropriate management for the patient must be personalized, whether it is by cesarean hysterectomy or interval hysterectomy,  as each has risks and benefits.